Re-Animalizing Animal Farm: Challenging the “Anthropo-Allegorical” in Literary and Pedagogical Discourse and Practice - Drew, John (Humanimalia, 2022)
Interpretations of George Orwell’s Animal Farm have been almost exclusively focused on anthropocentric allegory in the text and what I call the anthropo-allegorical interpretive frame. Given Animal Farm’s iconic and enduring status in English classrooms, I unpack this process, particularly how it is informed and perpetuated by the persistence of human exceptionalism rooted in the humanist literary tradition, and hegemonic approaches to education. I employ Derridean deconstruction to critique the humanist and educational legacies that inform the largely homogenized and de-animalized interpretation and pedagogical applications of Animal Farm. Then I argue for a new, hybridized reading — and teaching — that moves beyond the anthropocentric and toward a more-than-human interpretive and pedagogical orientation that speaks to the oppressions and challenges confronting multiple species, including, but not confined, to our own.